2017
DOI: 10.20937/rica.2017.33.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Síntesis De Arseniatos De Calcio (Guerinita, Haidingerita Y Farmacolita) Morfológicamente Similares a Los Encontrados en Suelos Contaminados

Abstract: Palabras clave: arsénico, arseniatos sintéticos, hábito cristalino, difracción de rayos X, microscopía electrónica de barrido, precipitación

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Cycles of dissolution and precipitation of secondary arsenate minerals formed in soil after irrigation may also account for the accumulation of As in the topsoil and the vertical migration of As. Highly soluble arsenate minerals, such as haidingerite (CaHAsO 4 ·H 2 O; pk sp = 10 −4.79 ) and pharmacolite (CaHAsO 4 ·2H 2 O; pk sp = 10 −4.68 ), in addition to guerinite (Ca 5 H 2 (AsO 4 ) 4 ·9H 2 O; pk sp = 10 −30.69 ) have been found in the old abandoned smelter in Matehuala, as a result of the precipitation of As in a calcium-rich environment [ 64 , 66 , 67 ]. Previous studies have shown that As is highly soluble in water, and the more gypsum the soil contains, the lower the solubility of As, while higher calcite results in higher dissolution [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cycles of dissolution and precipitation of secondary arsenate minerals formed in soil after irrigation may also account for the accumulation of As in the topsoil and the vertical migration of As. Highly soluble arsenate minerals, such as haidingerite (CaHAsO 4 ·H 2 O; pk sp = 10 −4.79 ) and pharmacolite (CaHAsO 4 ·2H 2 O; pk sp = 10 −4.68 ), in addition to guerinite (Ca 5 H 2 (AsO 4 ) 4 ·9H 2 O; pk sp = 10 −30.69 ) have been found in the old abandoned smelter in Matehuala, as a result of the precipitation of As in a calcium-rich environment [ 64 , 66 , 67 ]. Previous studies have shown that As is highly soluble in water, and the more gypsum the soil contains, the lower the solubility of As, while higher calcite results in higher dissolution [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Los MP se encuentran generalmente como componentes naturales de la corteza terrestre, en forma de minerales, sales u otros compuestos, estos no pueden ser degradados o destruidos fácilmente de forma natural o biológica ya que no tienen funciones metabólicas específicas para los seres vivos (Hernández et al, 2017). Los MP, se encuentran generalmente en bajas concentraciones en el ambiente, aunque, como resultado de las actividades antropogénicas, sus niveles se han incrementado (Liu et al, 2018), ocasionando contaminación en los ecosistemas expuestos a estos.…”
Section: Introductionunclassified